Purification and immunogenicity of hemagglutinin from highly pathogenic avian influenza virus H5N1 expressed in Nicotiana benthamiana - Pua, Teen-Lee; Chan, Xiao Ying; Loh, Hwei-San; Omar, Abdul Rahman; Yusibov, Vidadi; Musiychuk, Konstantin; Hall, Alexandra C.; Coffin, Megan V.; Shoji, Yoko; Chichester, Jessica A.; Bi, Hong; Streatfield, Stephen J. (Taylor & Francis, 2017)
Highly pathogenic avian influenza (HPAI) H5N1 is an ongoing global health concern due to its severe sporadic outbreaks in Asia, Africa and Europe, which poses a potential pandemic threat. The development of safe and cost-effective vaccine candidates for HPAI is considered the best strategy for managing the disease and addressing the pandemic preparedness. The most potential vaccine candidate is the antigenic determinant of influenza A virus, hemagglutinin (HA). The present research was aimed at developing optimized expression in Nicotiana benthamiana and protein purification process for HA from the Malaysian isolate of H5N1 as a vaccine antigen for HPAI H5N1. Expression of HA from the Malaysian isolate of HPAI in N. benthamiana was confirmed, and more soluble protein was expressed as truncated HA, the HA1 domain over the entire ectodomain of HA. Two different purification processes were evaluated for efficiency in terms of purity and yield. Due to the reduced yield, protein degradation and length of the 3-column purification process, the 2-column method was chosen for target purification. Purified HA1 was found immunogenic in mice inducing H5 HA-specific IgG and a hemagglutination inhibition antibody. This paper offers an alternative production system of a vaccine candidate against a locally circulating HPAI, which has a regional significance.